Identification of an IL‐1‐induced gene expression pattern in AR+ PCa cells that mimics the molecular phenotype of AR− PCa cells. Issue 8 (11th March 2018) - Thomas‐Jardin, Shayna E.; Kanchwala, Mohammed S.; Jacob, Joan; Merchant, Sana; Meade, Rachel K.; Gahnim, Nagham M.; Nawas, Afshan F.; Xing, Chao; Delk, Nikki A.
Abstract : Background: In immunosurveillance, bone‐derived immune cells infiltrate the tumor and secrete inflammatory cytokines to destroy cancer cells. However, cancer cells have evolved mechanisms to usurp inflammatory cytokines to promote tumor progression. In particular, the inflammatory cytokine, interleukin‐1 (IL‐1), is elevated in prostate cancer (PCa) patient tissue and serum, and promotes PCa bone metastasis. IL‐1 also represses androgen receptor (AR) accumulation and activity in PCa cells, yet the cells remain viable and tumorigenic; suggesting that IL‐1 may also contribute to AR‐targeted therapy resistance. Furthermore, IL‐1 and AR protein levels negatively correlate in PCa tumor cells. Taken together, we hypothesize that IL‐1 reprograms AR positive (AR + ) PCa cells into AR negative (AR − ) PCa cells that co‐opt IL‐1 signaling to ensure AR‐independent survival and tumor progression in the inflammatory tumor microenvironment. Methods: LNCaP and PC3 PCa cells were treated with IL‐1β or HS‐5 bone marrow stromal cell (BMSC) conditioned medium and analyzed by RNA sequencing and RT‐QPCR. To verify genes identified by RNA sequencing, LNCaP, MDA‐PCa‐2b, PC3, and DU145 PCa cell lines were treated with the IL‐1 family members, IL‐1α or IL‐1β, or exposed to HS‐5 BMSC in the presence or absence of Interleukin‐1 Receptor Antagonist (IL‐1RA). Treated cells were analyzed by western blot and/or RT‐QPCR. Results: Comparative analysis of sequencing data from the AR + LNCaP PCa cell line versus the AR − PC3 PCa cell line reveals an IL‐1‐conferred gene suite in LNCaP cells that is constitutive in PC3 cells. Bioinformatics analysis of the IL‐1 regulated gene suite revealed that inflammatory and immune response pathways are primarily elicited; likely facilitating PCa cell survival and tumorigenicity in an inflammatory tumor microenvironment. Conclusions: Our data supports that IL‐1 reprograms AR + PCa cells to mimic AR − PCa gene expression patterns that favor AR‐targeted treatment resistance and cell survival.